010 An example of evaluation of the professional practice leading to the improvement of care: the hospital stroke network. (23rd September 2015) - Osseby, G V; Béjot, Y; Chantegret, A; Durier, J; Honnart, D; Roy, H; Ricolfi, F; Gerbet, J Y; Bernard, A; Moreau, T; Giroud, M; Freysz, M
Abstract : Context: The management of acute stroke has become a structuring model in hospital organisation with the aim to improve the acute care of stroke. Stroke has become a medical emergency since the arrival of new active treatments in cerebral infarction. Fibrinolysis, for example, needs to be administered within the first 3 hours following admission to a stroke unit. The fact that stroke is a race against time is a new reality for carers. In contrast, the consequences of a poorly organised network may be severe. If fibrinolysis were used in all of the eligible cases of cerebral infarction, we could avoid 7500 deaths or severe handicap in France every year. Objectives: What triggered our interest in setting up the Professional Practice Evaluation (PPE) was the realisation in 2006 that in Dijon University Hospital only a small number of interventions involved fibrinolysis (a mean of 12 per year). The principal aim of the PPE was to identify the intrahospital factors that led to delay in admission to the Stroke Unit at Dijon CHU, while the secondary objective was to increase the use of fibrinolysis every year. Methods: All of those involved in the stroke network were trained according to a standardised protocol from 01 January 2006 to 30 September 2006: Staff working in the emergency room, imaging services, biology laboratory, ambulance and transportation services and stroke unit. The indicators, which were compared before and after the PPE, were the following: the delay to imaging, to biological results, to arrival at the stroke unit and the number of fibrinolysis. This prospective work was performed from 01 January 2006 to 30 September 2006, and was evaluated in 2007, and the data were compared to prior data collected since 1985 by the Dijon Stroke Registry. Results: We observed the following results: the proportion of imaging performed within the first 3 hours rose from 46% to 83 %; the mean delay to imaging decreased from156 min to 115 min, the time from arrival to imaging dropped from 87 to 37 min; the time between arrival and biological results decreased from 70 to 32 min; the mean annual number of fibrinolyses performed, around 12 per year between 2003 to 2006, tripled in 2007 and by 6 in 2008. Discussion: The training of the different professionals dramatically improved all the parameters evaluated, leading to a huge increase in the number of fibrinolyses, and inestimable benefits for stroke patients. Moreover, all the services that were considered unsatisfactory, such as imaging, biological analyses and ambulance, reacted positively, which made it possible to improve the parameters. We found that carers were willing to revise their usual practices without a feeling of guilt, and thus generated a huge improvement in the whole care process. Perspectives: We are evaluating the benefits in terms of the decrease in mortality and handicap since the implementation of PPE. Conclusion: We have demonstrated that at no extra cost it is possible to improve a stroke network due to awareness teaching and training of the different carers, the recognition of their role and work, their responsibilities, leading to measurable progress in treatment and increased job satisfaction for carers. Contexte: La prise en charge des AVC est devenue un modèle structurant dans l'organisation des hôpitaux pour optimiser la prise en charge de cette maladie. L'AVC est devenu une urgence médicale du fait de l'arrivée de thérapeutiques actives dans l'infarctus cérébral avec la fibrinolyse intraveineuse par rt-Pa, à condition d'être appliquées dans les 3 premières heures dans une Unité Neuro-Vasculaire (UNV). La notion d'une course contre la montre est une réalité dont chaque acteur de la prise en charge des AVC doit avoir conscience. A l'opposé, les conséquences d'une prise en charge non organisée peuvent être graves. Si tous les infarctus cérébraux éligibles à une fibrinolyse bénéficiaient de cette thérapeutique, 7 500 décès ou handicap sévère pourraient être évités en France chaque année. Objectifs: L'élément déclencheur qui a suscité en 2006 notre démarche d'une Evaluation des Pratiques Professionnelles (EPP) repose sur le constat du faible nombre de fibrinolyses effectuées au CHU de Dijon avec une moyenne de 12 fibrinolyses par an. L'objectif principal de notre EPP a été d'identifier les déterminants intra-hospitaliers à l'origine du retard d'admission à l'UNV du CHU de DIJON tandis que l'objectif secondaire a été l'augmentation du nombre de fibrinolyses chaque année. Methodes: L'ensemble des intervenants de la filière a été sensibilisé et formé entre le 01/01/2006 et le 30/03/2006: le personnel soignant du Service Régional d'Accueil des Urgences, du Scanner, du Service de Biochimie, du Service des Ambulanciers et de Brancardage et de l'UNV. Les indicateurs retenus pour l'évaluation de la filière avant et après formation, ont été: le délai d'obtention du scanner, le délai d'obtention des examens biologiques, le délai d'arrivée à l'UNV et le nombre de fibrinolyses effectué. Ce travail prospectif, effectué du 01/01/2006 au 30/09/2006 et évalué en 2007, a permis de comparer les données antérieures à la formation, recueillies par le Registre Dijonnais des AVC qui fonctionne depuis 1985. Resultats: Les résultats sur les indicateurs ont été les suivants: le taux de scanners effectué dans les 3 premières heures est passé de 46 % à 83 %; le délai moyen d'imagerie est passé de 109 à 54 minutes; le délai entre l'appel et l'imagerie a diminué de 156 à 115 minutes; le délai entre l'arrivée et l'imagerie a chuté de 87 à 37 minutes; le délai entre l'arrivée et l'obtention des résultats biologiques est passé de 70 à 32 minutes; le nombre moyen de fibrinolyse annuelle effectué entre 2003 et 2006 compris entre 10 et 12, a été multiplié par 3 en 2007, par 6 en 2008. Discussion: Les 6 mois de formation des différents maillons de la filière AVC ont permis indiscutablement d'améliorer tous les paramètres mesurés, aboutissant à une augmentation remarquable du nombre des fibrinolyses, c'est-à-dire un service médical rendu aux patients inestimable. D'autre part, les indicateurs qui avaient été analysés comme insuffisants, comme l'accès au scanner, l'accès à l'USINV, l'accès à la biologie, aux ambulanciers et au brancardage, ont suscité des réponses positives qui ont permis d'améliorer tous les indicateurs. Nous avons observé une remise en cause non culpabilisante des différents intervenants aboutissant à une amélioration active de l'ensemble de la filière. Perspectives: Nous sommes en train d'évaluer la gain en terme de baisse de la mortalité et du handicap depuis cette EPP. Conclusion: A moyens constants, nous avons démontré qu'il était possible d'améliorer l'efficience d'une filière intra-hospitalière pour les AVC par la sensibilisation et la formation ciblée des différents acteurs concernés, la reconnaissance de leur rôle et de leur travail et leur responsabilisation aboutissant à une amélioration des soins et valorisante pour les professionnels de santé.